PENGARUH PERTUMBUHAN PERUSAHAAN, STRUKTUR ASET, RISIKO BISNIS DAN FREE CASH FLOW TERHADAP KEBIJAKAN HUTANG (Studi pada Perusahaan BUMN Go Public yang terdaftar di BEI) - Farah Fadhilah; Iwan Setiadi; Henny Mulyati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This research aims to analyze the correlation of corporate growth, asset structure, business risk and free cash flow with debt policy. This research was conducted on SOEs companies Go Public registered in IDX period 2015 - 2019. This research sample used purposive sampling method. This research method uses causal research design. The data used is secondary data from the company's annual report. The analysis technique used is multiple linear regression analysis. The results of this research show that the company's growth is negatively correlated with debt policy. Asset structure is negatively correlated with debt policy. Business risk is negatively correlated with debt policy. Free cash flow is not significantly correlated with debt policy. Multiple linear regression analysis shows that the company's growth, asset structure, business risk, and free cash flow are simultaneously positively correlated with debt policy.